(untitled) (Journal of Contemporary Issues in Accounting, 2024)
The study investigated how the oil and the non-oil revenue of the Federal Government affects the Economy of Nigeria. The independent variables of this study are oil revenue, non-oil revenue, allocation from federation account, while dependent variable is real gross domestic product. The study adopted ex-post facto research design. The study covered the period 1981-2023, hence, maximizing the secondary source of data (time series data) collection that were collated from the CBN statistical bulletin and the National Bureau of Statistics (NBS) of various years. Relevant hypotheses were tested using the Ordinary Least Square analytical technique on the EVIEWS 10 statistical software. The results obtained revealed that generally, oil revenue had a negative and non-significant effect on real gross domestic product at (p> 0.05) of Nigeria during the period. On the other hand, it was discovered that the non-oil revenue and the allocation from federation account both had a positive and significant effect on real gross domestic product at (p<0.05), thereby also attesting to the largely ignored enormous contributions of the informal sector and vice versa. The study concluded that proper allocation and judicious use of these funds can stimulate economic activities at various levels of government, enhance infrastructure development, ensure a safer business environment and improve public services, all of which will no doubt contribute immensely to economic growth in Nigeria. The study recommended that, Nigeria need to prioritize commendable investment by way of diversification into non-oil production-based sectors such as agriculture, technology, and manufacturing, taking advantage of the iverhelming and teaming number of participants in the informal sector towards checking and reducing the country’s unnecessary and over dependence on oil revenue and imports. Government should also come up with implementable, self-accountability enabled and transparency oriented policies that readily enhance the full collection and management of non-oil revenues in Nigeria. Lastly, the National Assembly should ensure that allocations from the federation account are transparently managed, with strict oversight to prevent mismanagement and ensure funds are used for developmental projects that benefit the economy.